2014
DOI: 10.4161/cl.28928
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-2 mediates apical endosome transport during epithelial lumen formation

Abstract: Apical lumen formation is a key step during epithelial morphogenesis of tubular organs. Appropriate transport and targeting of apical proteins to the apical membrane initiation site (AMIS) plays a crucial role in establishing a solitary, central lumen. FIP5, a Rab11-interacting protein, is an important regulator that directs apical endosome trafficking along microtubules toward the AMIS during cytokinesis. However, it is unknown which molecular motor(s) transports FIP5-positive apical endosomes during lumen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…In a recent study, it was shown that the AMIS forms around the midbody during late telophase and that Rab11 effector protein FIP5, and endosomes containing apical proteins associated with it, are all transported to the AMIS along central spindle microtubules. 41 Then, these FIP5-endosomes fuse with the plasma membrane at the cleavage furrow neighboring the AMIS, thus supplying apical components (Crumbs-3a and glycoprotein135 (gp135)) needed for the formation and progression of the emerging lumen (Fig. 2).…”
Section: Rab11 During Cell Division and Amis Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, it was shown that the AMIS forms around the midbody during late telophase and that Rab11 effector protein FIP5, and endosomes containing apical proteins associated with it, are all transported to the AMIS along central spindle microtubules. 41 Then, these FIP5-endosomes fuse with the plasma membrane at the cleavage furrow neighboring the AMIS, thus supplying apical components (Crumbs-3a and glycoprotein135 (gp135)) needed for the formation and progression of the emerging lumen (Fig. 2).…”
Section: Rab11 During Cell Division and Amis Formationmentioning
confidence: 99%
“…Additionally, it was demonstrated that Kinesin-2 molecular motor directly binds to FIP5, thus mediating the delivery of FIP5-endosomes to the AMIS along central spindle microtubules during telophase. 41 FIP5 also binds sorting nexin 18 (SNX18). In particular, this interaction is needed for apical endocytic carrier formation and lumen formation.…”
Section: Rab11 During Cell Division and Amis Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, kinesin-2 was shown to be involved in the delivery of Rab11-FIP5 to the cleavage furrow of epithelial cells (43), but whether Rip11 associates with kinesin-2 or another motor protein is currently unknown. Alternatively, 14-3-3 might regulate the C2 domain of Rip11 and its capacity to bind phospholipids, but more work will be required to assess these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…We have created a protocol for 3D-time-lapse analysis of apical lumen formation using Madin-Darby canine kidney (MDCK) cells [3, 9]. Using this technique we were able to determine that cingulin is one of the first proteins recruited to the AMIS during late telophase, and that the Rab11/FIP5-endosomes are transported after AMIS formation around the midbody [3].…”
Section: Introductionmentioning
confidence: 99%